Excess body weight and age associated with the carriage of fluoroquinolone and third‐generation cephalosporin resistance genes in commensalEscherichia colifrom a cohort of urban Vietnamese children. Issue 10 (October 2018) - Thi Quynh Nhi, Le; Thanh Tuyen, Ha; Duc Trung, Pham; Do Hoang Nhu, Tran; Duy, Pham Thanh; Hao, Chung The; Thi Thanh Nhan, Nguyen; Vi, Lu Lan; Thi Diem Tuyet, Hoang; Thi Thuy Tien, Tran; Van Vinh Chau, Nguyen; Khanh Lam, Phung; et al.
Abstract : Purpose. : Antimicrobial‐resistant bacterial infections in low‐ and middle‐income countries (LMICs) are a well‐established global health issue. We aimed to assess the prevalence of and epidemiological factors associated with the carriage of ciprofloxacin‐ and ceftriaxone‐resistant Escherichia coli and associated resistance genes in a cohort of 498 healthy children residing in urban Vietnam. Methodology. : We cultured rectal swabs onto MacConkey agar supplemented with resistant concentrations of ciprofloxacin and ceftriaxone. Additionally, we screened meta‐ E. coli populations by conventional PCR to detect plasmid‐mediated quinolone resistance (PMQR)‐ and extended‐spectrum β‐lactamase (ESBL)‐encoding genes. We measured the associations between phenotypic/genotypic resistance and demographic characteristics using logistic regression. Results/Key findings. : Ciprofloxacin‐ and ceftriaxone‐resistant E. coli were cultured from the faecal samples of 67.7 % (337/498) and 80.3 % (400/498) of children, respectively. The prevalence of any associated resistance marker in the individual samples was 86.7 % (432/498) for PMQR genes and 90.6 % (451/498) for β‐lactamase genes. Overweight children were significantly more likely to carry qnr genes than children with lower weight‐for‐height z‐scores [odds ratios (OR): 1.24; 95 % confidence interval (CI): 10.5‐1.48 for each unit increase in weight for height; P =0.01]. Additionally, younger children were significantly more likely to carry ESBL CTX‐M genes than older children (OR: 0.97, 95 % CI: 0.94‐0.99 for each additional year, P =0.01). Conclusion. : The carriage of genotypic and phenotypic antimicrobial resistance is highly prevalent among E. coli in healthy children in the community in Vietnam. Future investigations on the carriage of antimicrobial resistant organisms in LMICs should focus on the progression of carriage from birth and structure of the microbiome in obesity.